Analisis Genom untuk Identifikasi Penyakit Langka di Indonesia - Dedy Arisjulyanto; Gerson Andrew Warnares (Journal of New Trends in Sciences, 2023)
Rare diseases present a significant challenge in diagnosis due to their low prevalence and the limited awareness among healthcare professionals. The emergence of genomic technologies, particularly Next-Generation Sequencing (NGS), has revolutionized the diagnosis of rare diseases by enabling the identification of genetic variations associated with these conditions. This technology offers improved accuracy and speed compared to traditional clinical diagnostic methods, which are often time-consuming and insufficient for rare genetic conditions. This study explores the application of genomic technology in identifying rare diseases in Indonesia, highlighting its effectiveness, accuracy, and the challenges involved in its implementation. The research employed genomic testing techniques, including whole-genome sequencing (WGS), to identify genetic mutations associated with rare diseases in patients. The findings of the study demonstrate that genomic technology significantly reduces the time required for diagnosis, providing a more comprehensive understanding of the genetic conditions. Diseases such as Diphyllobothriasis and Sparganosis, which are rarely diagnosed through traditional clinical methods, were successfully identified using genomic technologies. However, challenges persist in the implementation of genomic technology in Indonesia, including limited infrastructure, high costs, and a lack of specialized training for healthcare professionals. Despite these barriers, the findings underscore the potential of genomic technologies to improve the diagnosis and management of rare diseases in Indonesia. The study concludes by recommending further investments in infrastructure, the training of healthcare professionals, and the development of supportive policies to facilitate the widespread adoption of genomic technologies in the healthcare system, particularly for the diagnosis of rare diseases.